Comparative use of forest habitats by roe deer and moose in a human-modified landscape in southeastern Norway during winter - Torres, Rita Tinoco (2019)
The negative impact of anthropogenic disturbance and land-use changes on large mammals is generally recognized within conservation biology. In southeastern Norway, both moose (Alces alces) and roe deer (Capreolus capreolus) occur throughout humanmodiﬁed landscapes, facilitating an interesting comparative study of their habitat use. By using pellet group counts, we looked at the importance of forest structure, vegetation characteristics and human disturbance (e.g., distance to the nearest house, nearest paved road, and nearest edge between ﬁeld and forest) in shaping the winter distribution of both species at multiple spatial scales, in non-agricultural habitats. Moose occurred more often in areas with higher densities of heather and Vaccinium sp. in the ground layer, and used areas with more open forest structure. The proportion of built-up areas, within a 1,000-m buﬀer, negatively inﬂuenced moose occurrence. Roe deer occurred more often in areas with deciduous trees and patches with juniper and Vaccinium sp. in the ground layer, used areas near roads less, but were signiﬁcantly associated with areas near the ﬁeld–forest ecotone. The proportion of built-up areas positively inﬂuenced roe deer distribution within a 2,500-m buﬀer. Roe deer seem to be able to persist in more human-dominated landscapes, possibly due to the availability of ﬁeld–forest edges providing both high quality fodder and cover in close proximity. Moose, on the contrary, did not show any preference for areas associated with human disturbance, and their distribution was only associated with patches providing food.